“PENDIDIKAN UNTUK SEMUA” DALAM KAJIAN ISLAM - Muzammil Muzammil (Ta`Limuna: Jurnal Pendidikan Islam, 2013)
National education has not succeeded to the principles of "education for all" as outlined in the constitution. Already mentioned in the constitution, that Article 28 C Paragraph (1) which states, Everyone has the right to develop themselves through the fulfillment of basic needs, are entitled to education and to benefit from science and technology, arts and culture, for improving the quality of life and for the welfare of the people humans. Unfortunately this does not yet have a constitutional right to equal every citizen.